SIGNIFICANCE OF BASELINE ACE ACTIVITY IN PATIENTS WITH METABOLIC SYNDROME WHEN ADMINISTRATION OF ACE INHIBITORS AND IMIDAZOLINE AGONISTS IS CONSIDERED - T. V. Aparina; A. N. Britov; E. A. Dilakyan; V. A. Metelskaya; O. A. Gomazkov (Российский кардиологический журнал, 2001)
Significance of baseline ACE activity in patients with metabolic syndrome when administration of ACE inhibitors and imidazoline agonists is considered.